The gallery of vanished husbands [large type] - Solomons, Natasha (Center Point Large Print, 2013)
London, 1958. When Juliet Montague's husband disappears, so does she. As far as her Jewish community is concerned, she is invisible. Until, on her thirtieth birthday, she does something unexpected. Instead of buying a fridge, she impulsively spends her savings on a portrait of herself. The painting leads Juliet out of suburbia and into the heady art scene of London, where she proves an astute spotter of talent. Yet she remains an outsider in both her worlds: a mother of two, drawn to a reclusive artist who never leaves Dorset, and unable to feel free until she has tracked down her husband--a quest that leads her to California and a shocking discovery. This is the captivating tale of an unusual woman's journey through life, each stage hinged on a portrait. Written with infectious verve and humor, it confirms Natasha Solomons as an exceptionally talented young writer.